Myth and art : a correlation - Matthews, Celeste Deluvia (Rhodes University, Faculty of Humanities, Department of Fine Art, 1975)
The word myth evokes the same response as Lawrence's "snake at the water-trough"; the "voice of my education said it must be killed". We do so by confining it to Classicism or any of the diciplines. Myths in Classical language are Roman or Greek stories of fanciful or bawdy content, with naive or picturesque religious significance. A myth is not a story. There are many who interpret and explain myth. The fantasy doctors are applauded by the fantasy consumers. Intro. p. 1.
Keywords: Art and mythology